RESTAURANT COMPLETENESS EQUIPMENT STANDARD AT THE FOOD AND BEVERAGE SERVICE DEPARTMENT AT HARRIS HOTEL BATAM CENTER - Ribka Br Napitupulu; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Hotel is a company engaged in the field of services or services and uses part or all of the building to provide lodging, food and beverage services and other supporting services. Hotels are also one of the facilities that can support the progress of tourism in a place. Especially the hotel industry in the Riau Archipelago Province, namely Batam City. Batam City has star hotels, one of which is a four-star hotel, Harris Hotel Batam Center. Harris Hotel Batam Center has physical facilities, one of which is a restaurant, where as is known the second largest revenue in a hotel comes from selling food and beverages operating in a restaurant. A good restaurant does not only provide food and drinks but also must have a proper standard of tableware, complete with equipment such as Chinaware, Silverware, Glassware, Linen and Furniture. Without standard equipment completeness in a restaurant, it will hinder operational activities in it. Therefore, a restaurant needs to improve the standard of completeness of the equipment in it and can help the production process properly and correctly. Therefore, this study aims to find out how the completeness of Harris Café restaurant equipment is standard. This study uses qualitative methods to analyze problems based on data collection techniques in the form of observation, interviews, and documentation. Based on the results of the research that has been done, for the whole of the results of the interviews and observation of the documentation, it is said that the standard of completeness of equipment at the Harris Café restaurant is in accordance with the standard of completeness of restaurant equipment. Keywords: Standard, Equipment Completeness, Restaurant